Molecular characterization of Streptococcus pyogenes group A isolates from a tertiary hospital in Lebanon - Tokajian, Sima T. (2014)
Streptococcus pyogenes [Group A Streptococcus (GAS)] is one of the most important human pathogens, responsible for numerous diseases with diverse clinical manifestations. As the epidemiology of GAS infections evolves, a rapid and reliable characterization of the isolates remains essential for epidemiological analysis and infection control. This study investigated the epidemiological patterns and genetic characteristics of 150 GAS isolates from a tertiary hospital in Lebanon by emm typing, superantigens (SAgs) detection, PFGE and antibiotic profiling. The results revealed 41 distinct emm types, the most prevalent of which were emm89 (16 %), emm12 (10 %), emm2 (9 %) and emm1 (8 %). Testing for the presence of superantigens showed that speB (87 %), ssa (36 %) and speG (30 %) were predominant. PFGE detected 39 pulsotypes when a similarity cut-off value of 80 % was implemented. Antibiotic-susceptibility testing against seven different classes of antibiotics showed that 9 % of the isolates were resistant to clindamycin, 23 % were resistant to erythromycin and 4 % showed the macrolide–lincosamide–streptogramin B (MLSB) phenotype. The emergence of tetracycline-resistant strains (37 %) was high when compared with previous reports from Lebanon. This study provided comprehensive evidence of the epidemiology of GAS in Lebanon, highlighting the association between emm types and toxin genes, and providing valuable information about the origin and dissemination of this pathogen.